KEARIFAN LOKAL MASYARAKAT DESA SUNGAI BAKAU BESAR LAUT DALAM PENGELOLAAN HUTAN MANGROVE KECAMATAN SUNGAI PINYUH KABUPATEN MEMPAWAH - Pratama, Adidtia; Idham, M; AM, Iskandar (JURNAL HUTAN LESTARI, 2018)
The increasing of deforestation cause community awareness to sustain the forest expecially in Sungai Bakau Besar Laut Village, through local wisdom. It can prevent the occurence of violations that contribute to deforestation. Therefore, the purpose of study was to know the characteristics of the society (age, education, occupation, gender) and the role of local wisdom in the management of mangrove forests in the Sungai Bakau Besar Laut Village. This study was conducted for 2 weeks. The method in this study was the qualitative. The determination of sample used the snowball sampling with interview technique. The data were analized with descriptive qualitative. The results showed that the management of mangrove forests by Sungai Bakau Besar Laut community did not apply an unwritten rules but apply a written rules as local wisdom. An unwritten rules in the Sungai Bakau Besar Laut community included the robo - robo rituals and habits such as a decision making to be discussed, so it could solve the problems.Keyword : Local Wisdom, Mangrove Forest, Society.